A research on intelligent agent system for fashion clothing using Kansei Engineering / Anitawati Mohd Lokman - Mohd Lokman, Anitawati (Research Management Institute (RMI), 2011)
The study intends to implement Kansei Engineering in the design of an intelligent agent system for fashion clothing. The proposed system will read potential buyer's constraints, such as purpose, desire, age, and budget. The system will process the data and retrieve suitable fashion clothing from the database according to the results of Kansei evaluation and social constraints. Ultimately, the system will send clothing details to an avatar that advise the details to buyer, and display a list of possible fashion clothing including details as proposal to the potential buyer.